Prediction of recidivism among “second timers” in the juvenile justice system: Efficiency in screening chronic offenders - Smith, William Rudolph (American journal of criminal justice, 1999)
Identification of small subgroups of high-risk juvenile offenders from the general population to target them for intervention has proved elusive. It is argued that second-time delinquents represent a group that can be efficiently screened for chronic offenders. With a sample of 298 second-time juvenile offenders, both prospective and retrospective risk instruments are found to predict chronic delinquent behavior well. It is proposed that such risk instruments be used to focus benign intervention on high-risk, second-time juvenile offenders.